2018
DOI: 10.1136/archdischild-2018-315289
|View full text |Cite
|
Sign up to set email alerts
|

Parental opinion of consent in neonatal research

Abstract: BackgroundNeonatal research, particularly neonatal emergency research is a challenging area, notably in relation to obtaining valid prospective informed consent. The aim of this study is to determine parental perceptions of the consent process involved in performing research in newborn care, to explore methods used to obtain consent and their acceptability to parents.MethodsA parental questionnaire was developed that examined attitudes towards research and hypothetical research studies, in which the acceptabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
(30 reference statements)
1
13
0
Order By: Relevance
“…Recently, professional stakeholders and parent representatives made recommendations to ensure effective communication in consent procedures in this setting [ 31 ]. Alternatively, other types of consent procedures avoiding recruitment during a stressful period (such as antenatal consent or deferred consent) could be explored [ 4 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, professional stakeholders and parent representatives made recommendations to ensure effective communication in consent procedures in this setting [ 31 ]. Alternatively, other types of consent procedures avoiding recruitment during a stressful period (such as antenatal consent or deferred consent) could be explored [ 4 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, McCarthy et al examined parental attitudes towards the appropriateness of different consent approaches for hypothetical studies with neonates. In this study, most parents preferred a prospective consent approach 31. Rich and Katheria, however, suggested that deferring consent for DR studies is acceptable for parents 32.…”
Section: Introductionmentioning
confidence: 75%
“…27 32 Informed consent setting Routine antenatal visits are a unique opportunity to provide general information to all future parents about neonatal research currently being conducted at the hospital. 33 For certain neonatal and maternal conditions, these visits can also be an opportunity to provide more specific information and discuss with parents the potential inclusion of their child into a study. 34 This may provide parents with more time to discuss compared with providing this information only at the time of inclusion.…”
Section: Points To Considermentioning
confidence: 99%